European Union farming systems: Insights for a more sustainable land use - Martinho, Vítor (2022)
The diversity of agricultural systems in European Union (EU) regions and countries is vast and vulnerable to the Common Agricultural Policy (CAP) reforms. The CAP instruments have suffered several significant changes over the last decades to take into account the new contexts from the various EU enlargements and problems caused by former measures. This dynamic evolution of the farming system calls for updated assessment to better understand the respective policy impacts and to support the design of new and adjusted instruments. In this context, with this research, the intention is to highlight the most recent characteristics of the EU farming system and to assess the respective impacts from CAP measures. To achieve these aims, statistical information was considered from the Farm Accountancy Data Network (FADN) which was exploited through linear programming models. The main findings reveal that EU subsidies have no implication on the structure of EU farming systems. In other words, the most profitable farming systems are the same whether they were provided with the CAP financial support or not, namely those from the 1st Pillar. On the other hand, the CAP rules condition the farmers’ options, sometimes towards adopting a more subsidised production, but with lower margins. These frameworks would not be problematic, if the farming systems were more socially and environmentally sustainable, but this is not always the case. In a future scenario of a farming sector which more regulated by the market and less so by the CAP instruments, the environmental impacts will be more short-term than medium or long-term, where the main problem will be with energy consumption.